Effect Of Direct Current Electroanaesthesia On Nile Tilapia (Oreochromis Niloticus) (Applied Biological Research, 2022)
The presentstudy was aimedto assessthe effects of direct current (DC)  on inducing the stage-IV anaesthesia in Nile tilapia (Oreochromis  niloticus). Underwater DC of different magnitudes viz., 30, 60, 90 and  200 V applied for 25 sec in all, except 200 V whereinexposure time  varied from 15 to 30 sec. Notably, the exposure to 30, 60, and 90 V  for 25 sec did not induce anaesthesia; while 200 V DC lead to  successful anaesthesia. Opercular movements in fishes exposed to  200 V after 1 min of recovery was significantly higher than before exposure value. Opercular movements sloweddown gradually; and  after 15 min of recovery no significant difference in opercular  movement was observed. Normal swimming activity and reactivity  to tactile stimuli were restored after 10 min of recovery. The results  suggest that DC at 200 V was effective in inducing anaesthesia in O  niloticus with fast induction (15-30 sec) and recovery period (20-55  sec). This revealed that the electro-anaesthesia technique used in  this study offer a cost-effective, safe and eco-friendly alternative of  chemical anaesthetics.
Keywords: Anaesthesia; direct current; opercular movements; induction; recovery period